Implementing the human right to science in the context of health-related data processing - Molnár-Gábor, Fruzsina (Journal of law and the biosciences, 2024)
This paper contributes to the exploration of the potential application of duties related to the diligent anticipation of the (imminent) harms and (potential) benefits to humans that scientific innovation engenders to health-related contexts. In particular, it addresses the intersection between the human right to science and health-related data processing, which plays a key role in the production, translation and implementation of biomedical knowledge. The first part of the paper provides a brief recap of the interpretation of the right to science based on Art. 15 (1) (b) of the United Nations International Covenant on Economic, Social and Cultural Rights (hereafter ICESCR or Covenant) and the resulting obligations for States in the context of health and related data processing. The second part of the paper defines the relevance of the ICESCR for EU Member States and the European Union. In the third part, theses are put forward on how the human right to science and the obligations under Art. 15 (1) (b) ICESCR influence the interpretation and application of the General Data Protection Regulation as secondary EU law. By examining the justifications for using the right to science to interpret EU data protection law and by providing interpretation and application guidance on the main data protection principles in the area of health-related data processing, taking this right into account, the aim is to shape the EU data governance framework to meet the requirements of this human right. In doing so, the paper aims to close the gaps in the interpretation and application of the main rules of EU data protection law. Such standardization in the health-related context can contribute to a coherent interpretation and application of existing rules by referring to this emerging human right. Against this background, the paper identifies governance measures that the EU legislator could take to guide the processing of health-related data in line with the requirements of the right to science.
Online veröffentlicht: 16. März 2024
Gesehen am 11.07.2024